Menyalurkan Bakat dan Imajinasi Anak melalui Lomba Mewarnai dan Peragaan Busana bagi Siswa TK dan SD di Desa Mekarjati - Caskani; Nurul Fathimah; Amilda Fitriani Nurafifah; Izzatun Naili; Faat Nasyiruddin; Nana Mulyana; Iik Indri Kurniati; Rina Asha Gayatri; Muhamad Bahrul Ullum Alluji (Sejahtera: Pengabdian Kepada Masyarakat, 2026)
It is important to develop children's creativity and imagination in order to support their cognitive, emotional, and social development from an early age. Creative and educational activities are a means of channeling this potential. This community activity aims to channel children's interests and talents through coloring competitions and fashion shows as part of a festival held to welcome the holy month of Ramadan in Mekarjati Village, Haurgeulis District, Indramayu Regency. This activity took place at the Mekarjati village hall on February 14, 2026, with 100 participants, consisting of 50 coloring contest participants and 50 fashion show participants, who came from kindergartens and elementary schools. This activity took place in several stages, namely preparation, implementation, and evaluation. The results of the activity showed that the participants displayed high enthusiasm during the event and received support from their parents and the local community. Through this activity, children had the opportunity to channel their creativity, strengthen their self-confidence, and develop their imagination. Thus, this activity is expected to be a positive means of supporting the development of children's interests and talents in the community..